2010
DOI: 10.1111/j.1743-6109.2009.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Erectile Dysfunction in the Obese Type 2 Diabetic ZDF Rat with Adipose Tissue-Derived Stem Cells

Abstract: Introduction Impotence, or erectile dysfunction (ED), is a major complication of type-II diabetes, and many diabetic men with ED are refractory to common ED therapies. Aim To determine whether autologous adipose tissue derived stem cells (ADSC) injected into the penis of impotent obese type-II diabetic rats survive and improve erectile function. Main outcome measures Intracorporal pressure (ICP) increase with cavernous nerve (CN) electrostimulation, immunohistochemistry, real-time PCR, and serum glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 39 publications
7
122
1
Order By: Relevance
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 86%
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 86%
“…In all of our published SC-for-ED studies we reported difficulties in finding the transplanted SCs in penile tissues even though the animals clearly demonstrated functional and structural improvements [13,22,23,26]. In studies published by others, intracavernously injected SCs were similarly difficult to find.…”
Section: Stem Cell Transplantationmentioning
confidence: 84%
“…Investigation of the long-term fate of ADSCs is required before human trials could be considered, although the lack of ADSCs in tissue sections observed for a 28-day follow-up period implies that the potential of these cells to persist and undergo malignant transformation is limited. 124 Second, Garcia and co-workers 125 observed improved erectile function in type-2 diabetic rats after autologous ADSC injection. This observation was based on decreased numbers of apoptotic cells in the corpus cavernosum, increased numbers of sinusoid ECs and increased expression of nNOS in the penile nerves.…”
Section: Adscsmentioning
confidence: 96%